In memory of the professor Viktor Vasilyevich Ryabov - G. P. Kotelnikov (Вестник Самарского университета: История, педагогика, филология)
On February 26, 2025, the scientific and pedagogical community suffered an irreplaceable loss: Viktor Vasilyevich Ryabov, a corresponding member of the Russian Academy of Education, Doctor of Historical Sciences, Professor, President of the Moscow City Pedagogical University (MCPU), and its founder, passed away